Explosion mechanism of aluminum powder mixed with low-concentration hydrogen. (26th July 2022) - Cheng, Yu-Chi; Zhao, Jue-Quan; Liao, Sheng-Wei; Shu, Chi-Min
Abstract: This paper examines dust explosion characteristics and mechanisms for aluminum powder (Alp) in four different low-concentration hydrogen environments (0%, 1%, 2%, and 4 vol%). The aluminum powder's combustion characteristics were determined and the minimum ignition temperature and minimum ignition energy were found to be 690 °C and 45 mJ, respectively. A 20-L apparatus was used to evaluate how the explosive characteristics varied under different hydrogen concentrations. The explosion pressure generated by 4 vol% H2 was ca. 8.3% stronger than an explosion in the air, and the explosion pressure rise rate showed an increase of 48%. In addition, the time to maximum rate of pressure rise was shortened in the mixed Alp/hydrogen experiment. The experimental residues were observed, and from this it was inferred that the explosion mechanism changed when a low concentration of H2 was present. Graphical abstract: Image 1 Highlights: Defined the characteristic combustion and explosion parameters of Al powder. Acquired Al powder explosion data for four different H2 concentrations. Inferred the explosion mechanism for Al powder mixed in the presence of low-level H2 . Analyzed residual Al powder samples after an explosion involving low-level H2 concentrations.